Analisis Kelayakan Bisnis Pengembangan Usaha Startup - Heidi Siddiqa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The rapid growth of the global startup ecosystem has created many opportunities and challenges. The purpose of this study is to analyze the business feasibility of startup business development. The research method used is a literature study or Library Research with a qualitative approach. The literature used is literature from research results or reviews presented in national and international scientific articles related to startups. The results showed that this analysis is a critical stage that helps startup founders to understand whether their business idea has the potential to succeed in a competitive business environment. By evaluating components such as market, financial, technical, management, and risk, business feasibility analysis provides a deep understanding of the potential and challenges that startups may face. Keywords: Business feasibility, Enterprise development, Startup